Mechanical Coffee Pulper Equipment Test - Jonsion Purba; Saipul Bahri Daulay; Achwil Putra Munir (Universitas Sumatera Utara, 2014)
Equipment test is one of agricultural processing. The research was aimed to test Arabica coffee from 3 different origin which is appropriated with Mechanical Coffee Pulper Equipment on their equipment capacity, percentage of damage coffee, percentage of unpulped coffee, percentage of coffee bean in skin drain and percentage of skin in bean pipe. The research was conducted from September to October 2013 in Agriculture Engineering Laboratory. Agriculture Faculty, Sumatera Utara University, Medan, using non-factorial completely randomized design (CRD). The parameters measured were equipment capacity, percentage of unpulped coffee, percentage of damage coffee, percentage of coffee bean in drain skin, and percentage of skin in skin pipe.The results showed that equipment capacity was 119,80 kg/hr, 157,00 kg/hr and 160,86 kg/hr. percentage was unpulped coffee of 16,50%, 6,83% and 15,50%, percentage of damage coffee was 5,30%,6,90% and 7,90%, percentage of coffee bean in skin drain was 3,20%, 4,76%, and 4,96%, percentage of skin in pipe bean was 2,93%, 2,50%, and 3,06% respectively. Key word: capacity, mechanic pulper equipment, coffee skin